Circulatory System - Jakab, Cheryl (North Mankato, MN Smart Apple, 2006)
What is blood? What makes your blood look red? How long are the blood vessels in your body? What happens during a heart attack?
Primary
Keywords: 1. Blood - Circulation; 2. Our body